Governmental venture capital: A social capital and principal-agent related examination for Belgium, The Netherlands, Luxembourg, Austria and Germany - Christian Schlamp (The Journal of Entrepreneurial Finance (JEF), 2023)
The underlying research study was concerned with public venture capital which is grounded in the assumption of market failure and financing gaps (Güllmann 2000; Brettel 2005) and associated with the risk of crowding-out (Colombo et al. 2016). In order to expand the research perspective and to shed new light on the public investors, this project was concerned with their strategy, with their social networks, their syndication rationales, their monitoring and mentoring in turnaround situations and their exit routes between 2015 and 2017. 67 governmental investors in Belgium, The Netherlands, Luxembourg, Austria and Germany were invited to participate in a fully structured survey. In addition, secondary data sources were examined regarding the developments of the venture capital markets, of the crowdfunding markets and of the business angels' investments in the underlying countries between the phase of the financial crisis and the recent COVID-19 pandemic. The data was analysed by means of descriptive statistics and the survey results were finally validated by an additional validation study. The results, inter alia, showed that the public investors maintained comprehensive networks with different types of network partners and that social capital (Burt 1993; Lin 1999) played an important role for their business and not the provision of financings alone. Nevertheless, the results also showed that the network size did not matter for exit success on a statistically significant level and that the recent developments on the macro level called the public involvement in question.
Keywords: G30; 650; Governmental venture capital; venture capital networks; syndication; monitoring and mentoring; social capital; technology financing; financial crisis; COVID-19 pandemic